2016
DOI: 10.1016/j.omega.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of MCDM methods for the assessment of sustainable housing affordability

Abstract: Mulliner, Emma and Malys, Naglis and Maliene, Vida (2016) A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractWhile affordability is traditionally assessed in economic terms, this paper tests a new assessment method that draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
249
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(261 citation statements)
references
References 69 publications
(86 reference statements)
2
249
0
10
Order By: Relevance
“…Ecosystem preservation [9,19,24,26,29,33,[60][61][62]64]. Quality of outdoor environment [14,19,30,31,35,36,39,64,65]. Housing density [9,14,32,33].…”
Section: Land Use Considerationsmentioning
confidence: 99%
“…Ecosystem preservation [9,19,24,26,29,33,[60][61][62]64]. Quality of outdoor environment [14,19,30,31,35,36,39,64,65]. Housing density [9,14,32,33].…”
Section: Land Use Considerationsmentioning
confidence: 99%
“…A sustainable built environment is, therefore, inseparable from attempts to build sustainable communities [14,[51][52][53][54][55][56][57][58]. Maliene and Malys [52] developed a model of sustainable housing development for sustainable communities, which can be adapted to any town and which will help to create healthy and attractive communities.…”
Section: Criteria Of a Sustainable Built Environment And The Assessmementioning
confidence: 99%
“…As sorting methods, ELECTRE TRI (also called the non-compensatory sorting model (Bouyssou & Marchant, 2007a;2007b)) and ELECTRE-SORT are used to assign alternatives to predefi ned categories (Mousseau et al, 2000;Ishizaka & Nemery, 2014). Similar schemes are also employed by other outranking relations sorting methods such as PROMSORT (Araz & Ozkarahan, 2005) and FlowSort (Nemery & Lamboray, 2008;Janssen & Nemery, 2013), which are based on the PROMETHEE method (Preference Ranking Organization Method for Enrichment Evaluation) (see Brans & Vincke, 1985), a well-known multiple criteria outranking method.…”
Section: Introductionmentioning
confidence: 99%
“…The classical TOPSIS method (see Jia et al, 2012;Ahmadi et al, 2014;Bilbao-Terol et al, 2014;Mulliner et al, 2016) and its extensions, such as interval TOPSIS (see Giove, 2002;Jahanshahloo et al, 2006;Dymova et al, 2013), fuzzy TOPSIS (see Awasthi et al, 2011;Awasthi & Chauhan, 2012;Bao et al, 2012;Ye & Li, 2014;Lee et al, 2014;Kusi-Sarpong et al, 2015;Şengül et al, 2015), interval-valued fuzzy TOPSIS (see Chen & Tsao, 2008;Ashtiani et al, 2009;Mokhtarian, 2015;Zhang & Xu, 2015), and grey TOPSIS (see Chen & Tzeng, 2004;Oztaysi, 2014;Siozinyte et al, 2014;Jiang et al, 2015), have demonstrated their capabilities and potentials in dealing with MCDM problems of various fi elds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation